Individual differences and Information Security Awareness. (April 2017) - McCormac, Agata; Zwaans, Tara; Parsons, Kathryn; Calic, Dragana; Butavicius, Marcus; Pattinson, Malcolm
Abstract: The main purpose of this study was to examine the relationship between individuals' Information Security Awareness (ISA) and individual difference variables, namely age, gender, personality and risk-taking propensity. Within this study, ISA was defined as individuals' knowledge of what policies and procedures they should follow, their understanding of why they should adhere to them (their attitude) and what they actually do (their behaviour). This was measured using the Human Aspects of Information Security Questionnaire (HAIS-Q). Individual difference variables were examined via a survey of 505 working Australians. It was found that conscientiousness, agreeableness, emotional stability and risk-taking propensity significantly explained variance in individuals' ISA, while age and gender did not. Findings highlighted the need for future research to examine individual differences and their impact on ISA. Results of the study can be applied by industry to develop tailored InfoSec training programs. Highlights: Emotional stability was positively associated with Information Security Awareness (ISA). Conscientiousness and agreeableness were positively associated with ISA. Individuals with a propensity to take fewer risks scored higher on ISA.